Immunomodulatory roles of selenium nanoparticles: Novel arts for potential immunotherapy strategy development - Chen, Gengshi; Yang, Fen; Fan, Shuhao; Jin, Hua; Liao, Kangsheng; Li, Xuemeng; Liu, Gan-Bin; Liang, Jing; Zhang, Junai; Xu, Jun-Fa; Pi, Jiang (Frontiers in Immunology, 2022)
Tumor, infectious diseases, and some important chronic diseases are the most threatening diseases to human lives. Traditional chemotherapy strategies used in clinic appear with lots of disadvantages due to the low targeting effects of drugs, which significantly restricts the drug potency, causes multiple dysfunctions in the body and even drives the emergence of diseases, immunotherapy can boost the body’s innate and adaptive defenses for more effective disease control and treatment. As a trace element, Selenium plays vital roles in human health by regulating the anti-oxidant defense, enzyme activity and immune response through various specific pathways. Profiting from novel nanotechnology, Selenium nanoparticles (Se NPs) have been widely developed to reveal great potential chemotherapy in anti-cancer, anti-bacterial and anti-inflammation treatment. More interestingly, increasing evidences have also shown that functional Se NPs can be applied for potential immunotherapy, which would achieve more effective treatment efficiency by combining with traditional chemotherapy. By directly interacting with innate immune cells, such as macrophages and dendritic cells, Se NPs can regulate innate immunological functions to intervene disease developments, which therefore boost the anti-cancer, anti-infection and anti-inflammation treatments. Moreover, Se NPs can also activate and recover NK cells and different T cells for adaptive immunity controls, and enhance their cytotoxic to combat cancer cells. Therefore, this review will summarize the application of Se NPs in immunotherapy, emphatically in tumors, infectious, inflammatory and underlying diseases. Furthermore, we will also discuss the advancing perspective of Se NPs based immunotherapy as a kind of novel intervention therapy to enhance the efficiency of current chemotherapies, which may be helpful to promote future research on nanotechnology-assisted immunotherapy and finally benefit the more effective disease treatments.